Sex Differences in the Blood Oxygen Level-Dependent Signal to Placebo Analgesia and Nocebo Hyperalgesia in Experimental Pain: A Functional MRI Study - Shi, Yu; Zhan, Hongrui; Zeng, Yanyan; Huang, Shimin; Cai, Guiyuan; Yang, Jianming; Wu, Wen (Frontiers in Behavioral Neuroscience, 2021)
Objective Placebo as well as nocebo responses are widely found in scientific research and clinical practice. Growing evidence suggests sex differences in placebo as well as nocebo responses. However, data concerning this question are still insufficient. This study examined whether the BOLD signals of two responses, as measured with fMRI, differ by sex under conditions of equivalent experimental pain perception. Method Thirty-one healthy volunteers (14 female) underwent 2 fMRI scans, once during a placebo intervention and once during a nocebo intervention, pseudo-randomly ordered, in an acute lower back pain (ALBP) model. We collect visual analogue scale (VAS) data after each scanning. fMRI data from different sex groups were subjected to functional connectivity (FC) analysis and behavioral correlation analysis (BCA). Results The results showed statistical differences in VAS scores between male and female participants, in both placebo and nocebo responses. Both groups also showed reduced FC in the pain associated network of the placebo response and elevated FC in the pain related network of the nocebo response. However, in the placebo condition male participants displayed increased FC in the ventromedial prefrontal cortex, parahippocampal gyrus (PHP), and posterior cingulate cortex (PCC); while female participants showed increased FC in the dorsolateral prefrontal cortex, the hippocampal gyrus (HP), as well as the insular cortex (IC). In the nocebo condition, male participants showed decreased FC in the PCC and HP; while female participants displayed decreased FC in the mid-cingulate cortex, thalamus (THS), and HP. The BCA results of the two groups were also different. Conclusion We found that the endogenous opioid system and reward circuit play a key role in sex differences of placebo response, and that anxiety and its secondary reactions may cause the sex differences of nocebo response.